(untitled) (Journal of Nepal Geological Society, 1998)
The Lesser Himalaya in the Pokhara region, western Nepal, comprises low grade metamorphic rocks of the Nawakot Complex in the south and mylonitic rocks of the Main Central Thrust Zone in the north. It is delimited in the north by the Main Central Thrust (MCT), which brings the kyanite gneisses of the Higher Himalayan Crystallines over the Lesser Himalayan metasediments. Cross-cutting pegmatite veins injected prior and posterior to the main deformation event are reported for the first time from the MCT Zone. The Phalebas Thrust, Lumle Thrust and the MCT are the major structural discordances, which divide the area into various tectonic zones with different style and intensity of deformation. At least three deformation events are recognised in each tectonic zone. Sense of shearing is always top to the south in the MCT Zone. The Higher Himalayan Crystallines and the Lesser Himalayan metasediments show marked differences both in history and grade of metamorphism. The gneisses of the Higher Himalayan Crystallines exhibit polyphase metamorphism. The older high grade (kyanite-grade) metamorphism formed pyrope-rich cores in garnets and plagioclase with An>20%. The younger retrograde metamorphism caused to recrystallise phengitic muscovite and to form retrograde chemical zoning in garnets. The Lesser Himalaya shows syn- to post-tectonic, garnet-grade, inverted prograde metarnrophism. The grade of metamorphism increases from chlorite zone in the south to the biotite zone below the Lumle Thrust and the garnet zone in the MCT Zone. The garnets show prograde zoning pattern, muscovite gradually becomes poor in celadonite component, biotite becomes rich in Ti-content, and Ca-amphiboles become rich in Na and K from south towards the MCT. Both the Lesser Himalayan metasediments and the Higher Himalayan Crystallines have experienced the late-stage weak regression due to uplift and erosion.